IMAGE, PERSON, AND THE PRECONCEIVED NOTION OF MONOTHEISM; A COMPARATIVE APPROACH - Axinciuc, Madeea (European Scientific Journal, ESJ, 2013)
﻿The study revisits, in a critical and creative manner pertaining mainly to philosophy of religion and comparative religion, the notions of image, idolatry, and person, laying emphasis on their tight connection to (re)defining and (re)tracing the essential features of monotheism. The preconceived, popular and/ or theological, misunderstanding of key-terms evoked in ‘monotheistic’ discourses or applied with regard to ‘other’ religious traditions (than the Abrahamic ‘monotheisms’) highlights the necessity to thoroughly and adequately re-approach the religious phenomenon and its various expressions in diverse traditions, by re-contextualizing, in scientific, non-apologetic and non-confessional ways, the relation with the ‘divine’ when envisaged as a unifying experience. In this framework, the connection with ‘the One’, the emergence of personal God, and the notion of ‘chosen people’ are attentively reconsidered.